Comparison of Two Kinds of Endurance Training Programs on the Effects of the Ability to Recover in Amateur Soccer Players - Rogan, Slavko (Asian J Sports Med, 2015)
BACKGROUND: High intensity intermittent aerobic exercise is an elementary endurance training exercise to build soccer endurance. Many studies exist with professional soccer players. But limited research has been conducted with amateur soccer players. OBJECTIVES: The aim of this study was to compare and assess the effects of the shuttle-run method and the Hoff-track method on the ability to recover in amateur soccer players within three weeks. PATIENTS AND METHODS: Two amateur soccer teams were randomly assigned to shuttle-run group (n = 24; SRG) (SRG: shuttle-run group) or Hoff-track group (n = 18; HTG) (HTG: hoff-track group). They performed 2 times/week over three weeks their program. SRG performed a 20 m high speed shuttle-run until exhaustion and HTG covered at their highest speed level an obstacle track. Before and after training the yo-yo intermittent recovery test level 2 (YYIRTL2) was conducted. RESULTS: Significant differences were observed within (P < 0.05) and between the groups (P = 0.06; ES = 0.50) in distance covering during YYIRTL2. CONCLUSIONS: Both training methods seem to improve the ability to recover in amateur soccer players within a short time period during the competition season.